Post Human and Female Cyborg in The Perfect Wife Novel By J.P. Delaney - Mufidah, Zakiyatul (Fakultas Ilmu Budaya, Universitas Mulawarman, 2022)
This study aims to reveal the situation of post human and the description of female cyborg in JP Delaney's novel The Perfect Wife, it also explains how the relationship between humans and cyborgs in this novel. The theory of cyborgism by Donna Harraway is applied to analyze the representation of post humanism as articulated through a female cyborg character. In addition, it is worth-studied as the female cyborg character is positioned in the context of husband-wife marriage. However, this study focuses on two descrition of the female cyborg who is predominantly influenced by typical gender stereotyping.Qualitative research is taken as the approach of this study. Data collection is mostly obtained by close reading technique, while the data analysis is done by applying the theory to analyze the texts taken from author’s narration and characters’ utterances within the novel. The results of this study confirm that the female cyborg character is created by a human has a great potential to replace the role of a human being physically, intellectually and abilities, and the relationship that occurs between cyborgs and humans. It also affirms that the female cyborg presented in the novel is created to satisfy man’s need and characterized to possess typical and stereotypical woman.